COI barcodes for the identification of anthropophilic Biting Midges (Diptera: Ceratopogonidae: Culicoides) from the Brazilian Amazon - Emanuelle DE SOUSA FARIAS; Moises Thiago DE SOUZA FREITAS; Sanmya Silva DOS SANTOS; Jokebede Melynda DOS SANTOS PAULINO-ROSA; Luiz DE SOUZA COELHO; Jordam William PEREIRA-SILVA; James Lee CRAINEY; Claudia María RÍOS-VELÁSQUEZ; Felipe Arley COSTA PESSOA (European Journal of Entomology, 2025)
The genus Culicoides is the best known of the family Ceratopogonidae. Hematophagous females of the genus typically feed on the blood of vertebrate animals and in the Brazilian Amazon often on the blood of human beings. Amazon region anthropophilic Culicoides bites can provoke allergic reactions and transmit Mansonella ozzardi as well as the Oropouche virus. Past integrated taxonomy studies, combining morphometric and molecular analyses, have revealed hidden disease vector biodiversity and cryptic species with epidemiological and disease control relevance and have provided new tools to assist with vector identification. For this study we used light traps set in 12 distinct sites from three different Amazon states: Rondonia (1 site), Amazonas (3 sites) and Para (8 sites). We captured 12 different species of Culicoides representing seven different subgenera: C. foxi, C. fusipalpis, C. hylas, C. insignis, C. plaumanni, C. pseudodiabolicus, C. ruizi, C. debilipalpis, C. glabrior, C. jurutiensis, C. paraensis, C. paucienfuscatus. Between two and nine specimens were barcoded of each species. Neighbor joining and Maximum likelihood phylogenetic analysis with these COI barcodes showed the utility of these barcode sequences for species identification by clustering the barcode sequences into bootstrap-supported, species-specific monophyletic groups. Although this barcoding analysis did not resolve relationships between the species studied, it did reveal cryptic diversity within C. paucienfuscatus, C. glabrior, C. plaumanni, C. insignis and C. pseudodiabolicus. Two-dimensional geometric morphometrics, using eight wing-vein landmarks, robustly separated the analyzed species and raised questions about the validity of the subgenus Haematomyidium. Importantly, our GM wing landmark analysis separated C. paraensis from all the other analyzed species suggesting this type of analysis could be harnessed for epidemiological monitoring of this key Amazon-region vector species.